Efek Pengungkapan Corporate Social Responsibility, Profitabilitas dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Ivani Yolinda Suleman; Yovita Ariani Winoto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research aims to analyze the influence of corporate social responsibility disclosure, profitability, and company size on company’s value or firm value. In this study, data was collected from all mining companies listed on the Indonesia stock Exchange from 2019 to 2022, taking into account data completeness and earnings throughout the observation period. The research results indicate that corporate social responsibility disclosure has no significant influence on firm value with a significance level of 0.973. However, there is a significant positive influence of profitability on firm value with a significance level of 0.000 and a positive t-value of 3.980. The influence of company size on firm value shows a negative influence with a significance level of 0.24 and a negative t value of -2.295.